2010
DOI: 10.1017/s0950268810001093
|View full text |Cite
|
Sign up to set email alerts
|

Changing species distribution and antimicrobial susceptibility pattern ofShigellaover a 29-year period (1980–2008)

Abstract: SUMMARYWe studied changes in species distribution and antimicrobial resistance patterns of Shigella during 1980-2008, using the Diarrhoeal Diseases Surveillance system of Dhaka Hospital of ICDDR,B. In hospitalized patients Shigella prevalence decreased steadily from 8-12 % in the 1980s to 3% in 2008. Endemic S. flexneri was the most commonly isolated species (54 %). Epidemic S. dysenteriae type 1 had two peaks in 1984 and 1993, but was not found after 2000, except for one case in 2004. The therapeutic options … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 17 publications
6
35
0
Order By: Relevance
“…No isolates of S. boydii and S. dysenteriae were identified. These results are in keeping with reports of previous studies in which S. flexneri was responsible for more than 50z of shigellosis cases (34)(35)(36).…”
Section: Discussionsupporting
confidence: 93%
“…No isolates of S. boydii and S. dysenteriae were identified. These results are in keeping with reports of previous studies in which S. flexneri was responsible for more than 50z of shigellosis cases (34)(35)(36).…”
Section: Discussionsupporting
confidence: 93%
“…Shigella was the second most isolated organism in Mirzapur, but was significantly lower in the other sites, especially Mirpur. A 2011 study conducted with 83,073 patients in Dhaka, revealed that the proportion of hospitalized patients with Shigella decreased steadily from 8% to 12% in 1980 to 3% in 2008 [32]. Our results also indicate that S. flexneri is the dominant circulating species; this finding supports reports previously indicating the dominance of S. flexneri in Bangladesh [32].…”
Section: Discussionsupporting
confidence: 88%
“…A 2011 study conducted with 83,073 patients in Dhaka, revealed that the proportion of hospitalized patients with Shigella decreased steadily from 8% to 12% in 1980 to 3% in 2008 [32]. Our results also indicate that S. flexneri is the dominant circulating species; this finding supports reports previously indicating the dominance of S. flexneri in Bangladesh [32]. The results from the study also illustrate that V. cholerae continues to be a major [33,34,35].…”
Section: Discussionsupporting
confidence: 87%
“…Previously efficacious antibiotics have become ineffective in treatment of the diseases due to emergence of multidrug resistance Shigella [13][14][15]. Consequently, the need for a safe and effective Shigella vaccine becomes more pressing and WHO has assigned a high priority to the development of vaccine against shigellosis [16,17].…”
Section: Introductionmentioning
confidence: 99%